2024
DOI: 10.1111/nph.19602
|View full text |Cite
|
Sign up to set email alerts
|

Major quality regulation network of flavonoid synthesis governing the bioactivity of black wolfberry

Youwei Du,
Huiya Ma,
Yuanyuan Liu
et al.

Abstract: Summary Black wolfberry (Lycium ruthenicum Murr.) contains various bioactive metabolites represented by flavonoids, which are quite different among production regions. However, the underlying regulation mechanism of flavonoid biosynthesis governing the bioactivity of black wolfberry remains unclear. Presently, we compared the bioactivity of black wolfberry from five production regions. Multi‐omics were performed to construct the regulation network associated with the fruit bioactivity. The detailed regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…This study has revealed that L. ruthenicum harbors a more abundant array of flavonoids and phenolic acids, as well as the highest concentration of antioxidant constituents, indicating that L. ruthenicum may possess superior antioxidant capabilities. This aligns with the findings of Du et al (2024) , who noted the heightened antioxidant activity and flavonoid content in L. ruthenicum sourced from Qinghai. Furthermore, the lower lipid content of L. ruthenicum may render it a more suitable choice for consumption by individuals adhering to high-fat diets.…”
Section: Discussionsupporting
confidence: 92%
“…This study has revealed that L. ruthenicum harbors a more abundant array of flavonoids and phenolic acids, as well as the highest concentration of antioxidant constituents, indicating that L. ruthenicum may possess superior antioxidant capabilities. This aligns with the findings of Du et al (2024) , who noted the heightened antioxidant activity and flavonoid content in L. ruthenicum sourced from Qinghai. Furthermore, the lower lipid content of L. ruthenicum may render it a more suitable choice for consumption by individuals adhering to high-fat diets.…”
Section: Discussionsupporting
confidence: 92%
“…Protein Expression and Purification. The prokaryotic expression system of MUC1 was performed following Du et al 24 The full coding sequencing of human MUC1 gene was ligated into the PGEX-4T vector for protein purification with GST-tag (Transheep Biotechnology, Shanghai, China). The positive 4T vector containing MUC1 was converted into BL21 (DE3), then isopropyl-D-thiogalactopyranoside (IPTG) was added to enhance MUC1 expression for 4 h at 37 °C.…”
Section: ■ Introductionmentioning
confidence: 99%